2004
DOI: 10.1111/j.1464-410x.2004.04933.x
|View full text |Cite
|
Sign up to set email alerts
|

Ileal orthotopic neobladder (modified Hautmann) via a shorter detubularized ileal segment: experience and results

Abstract: RESULTSWhile no patients died during surgery six died (mortality rate was 5%) in the first 30 days afterward (two of them from causes unrelated to the urinary diversion surgery). The early reoperation rate was 14%; there were early complications not requiring surgery in 40 (34%) and later reoperation rate was required in 20.6%. The mean (range) maximum neobladder capacity was 550 (310-720) mL, the maximum intravesical pressure at maximum capacity 26.4 (11-48) cmH 2 O, and the minimum and maximum flow rates 25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
7
43
2
6
Order By: Relevance
“…In our study PVR was 16.7 mL (0-140), compared to 40 (0-150) mL and 30 mL presented in two other studies 4,5 . The median maximal flow rate in our group was 22.1 mL/s (9.7-39.5) and in Sevin´s 4 study 17.5 mL/s (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 4 .…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In our study PVR was 16.7 mL (0-140), compared to 40 (0-150) mL and 30 mL presented in two other studies 4,5 . The median maximal flow rate in our group was 22.1 mL/s (9.7-39.5) and in Sevin´s 4 study 17.5 mL/s (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 4 .…”
Section: Discussioncontrasting
confidence: 53%
“…The median maximal flow rate in our group was 22.1 mL/s (9.7-39.5) and in Sevin´s 4 study 17.5 mL/s (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 4 . The difference is significant and expected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although nighttime continence rates and voiding intervals in our study are better than [16,18,19,20,21] or similar to [22,23] other techniques reported in the literature, nocturnal incontinence remains a noticeable problem in bladder substitution patients. After urinary bladder removal during radical cystectomy, loss of filling sensation and destruction of feedback mechanisms are naturally expected.…”
Section: Discussionmentioning
confidence: 52%
“…Sevin G [26] 2004 Ileal neobladder: periodical neobladder contractions Kulkarni J [9] 2003 Ileocecal neobladder: uninhibited bladder contraction or increase in reservoir pressure persistence of involuntary contractions Sigmoid: postvoid residual urine in neobladder Reddy PK [4] 1991 Sigmoid neobladder (Reddy): low neobladder capacity, lack of filling sensation, spontaneous neobladder wall contractions 8. Urethral pressure profile measurements were performed to assess the resting closure pressure of the sphincter (P clos.…”
Section: Methodsmentioning
confidence: 99%